Client reflections on confirmation and disconfirmation of expectations in cognitive behavioral therapy for generalized anxiety disorder with and without motivational interviewing. (30th September 2019) - Button, Melissa L.; Norouzian, Nikoo; Westra, Henny A.; Constantino, Michael J.; Antony, Martin M.
Abstract: Objective: Addressing methodological shortcomings of prior work on process expectations, this study examined client process expectations both prospectively and retrospectively following treatment. Differences between clients receiving cognitive behavioral therapy (CBT) versus motivational interviewing integrated with CBT (MI-CBT) were also examined. Method : Grounded theory analysis was used to study narratives of 10 participants ( N  = 5 CBT, 5 MI-CBT) who completed treatment for severe generalized anxiety disorder as part of a larger randomized controlled trial. Results: Clients in both groups reported and elaborated expectancy disconfirmations more than expectancy confirmations. Compared to CBT clients, MI-CBT clients reported experiencing greater agency in the treatment process than expected (e.g., that they did most of the work) and that therapy provided a corrective experience. Despite nearly all clients achieving recovery status, CBT clients described therapy as not working in some ways (i.e., tasks did not fit, lack of improvement) and that they overcame initial skepticism regarding treatment. Conclusions: Largely converging with MI theory, findings highlight the role of key therapist behaviors (e.g., encouraging client autonomy, validating) in facilitating client experiences of the self as an agentic individual who is actively engaged in the therapy process and capable of effecting change.